2015
DOI: 10.4239/wjd.v6.i14.1259
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin and diabetes mellitus

Abstract: Erythropoietin (EPO) is a 30.4 kDa growth factor and cytokine that governs cell proliferation, immune modulation, metabolic homeostasis, vascular function, and cytoprotection. EPO is under investigation for the treatment of variety of diseases, but appears especially suited for the treatment of disorders of metabolism that include diabetes mellitus (DM). DM and the complications of this disease impact a significant portion of the global population leading to disability and death with currently limited therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 253 publications
3
39
0
2
Order By: Relevance
“…EPO has the capacity to offer protection against a number of disease entities (208212) as well as enhanced biological activity (213, 214). For example, EPO has been reported to improve clinical outcome during development (215), neurodegenerative disorders (216), stroke (217222), aging (223), TBI (32, 224), vascular disease (217222), depression (208, 225), and metabolic disturbances (63, 211, 226, 227). …”
Section: Erythropoietin and The Modulation Of Mtormentioning
confidence: 99%
“…EPO has the capacity to offer protection against a number of disease entities (208212) as well as enhanced biological activity (213, 214). For example, EPO has been reported to improve clinical outcome during development (215), neurodegenerative disorders (216), stroke (217222), aging (223), TBI (32, 224), vascular disease (217222), depression (208, 225), and metabolic disturbances (63, 211, 226, 227). …”
Section: Erythropoietin and The Modulation Of Mtormentioning
confidence: 99%
“…EPO expression can be influenced by changes in oxygen tension and not by the concentration of red blood cells [28,34,39]. Expression of EPO also may be promoted by stimuli that are not related to hypoxia [40]. For example, agents that block inflammation in cerebral microglia have been recently shown to lead to the release of EPO [41] and xenon anesthesia in cardiac surgery can result in elevated EPO serum concentrations [42].…”
Section: Erythropoietin and Traumatic Brain Injury: Translating Expermentioning
confidence: 99%
“…It is worth mentioning that EPO due to its anti-apoptotic and tissue protective effects has long been used in treatment of chronic anemia (16) , myocardial infraction (17) , diabetes mellitus (18) , spinal cord injury (19) , acute lung injury (20) . Relatively recent studies showed that EPO can increase the VEGF expression in the injury sites, promotes new vessels formation and promptly heal wounds (20) .…”
Section: Introductionmentioning
confidence: 99%